Workshop on strengthening the implementation of the Climate Smart Governance Dashboard in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Jayamini, Kalpani; Madhushini, Dilshi (International Water Management Institute, 2024)
The CGIAR Climate Smart Governance (CSG) Dashboard has been developed by the International Water Management Institute (IWMI) in partnership with Sri Lanka's National Planning Department (NPD) and the Climate Change Secretariat (CCS) of the Ministry of Environment. The comprehensive tool to enhance disaster management strategies in Sri Lanka are being significantly supported by the Climate Smart Governance (CSG) dashboard. This dashboard provides data on climate-related hazards, population vulnerability, forecast climate scenarios, and sectorspecific information including water, health, agriculture, and ecosystems. It also includes data on infrastructure and climate-related projects, which is essential for coordinated mid- to long-term adaptation planning aligned with global development goals.